Flower-shaped micro-nano double-layer structure super-hydrophobic coating and preparation method thereof
By constructing the base layer on the substrate surface and applying modified reducing iron powder, a flower-like micro-nano double-layer structure superhydrophobic coating was prepared, which solved the problem of poor mechanical stability of the existing coating and achieved excellent mechanical stability and corrosion-resistant.
Patent Information
- Application Number
- CN202411598660.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-11
AI Technical Summary
The existing superhydrophobic surface coatings have problems such as poor wear resistance and poor bonding force with the substrate, which leads to insufficient mechanical stability and limits its practical application.
The preparation method of a flower-shaped micro-nano double-layer structure superhydrophobic coating is adopted. By constructing a base layer on the surface of the substrate and applying modified reduced iron powder thereon, heat treatment is carried out to form a superhydrophobic surface layer, thereby improving the mechanical stability of the coating. and superhydrophobic properties.
It realizes excellent mechanical stability and corrosion resistance of the superhydrophobic coating, enhances the bonding force with the substrate, improves the wear resistance and stain resistance of the coating, and extends the service life of the material.
Smart Images

Figure CN119426142A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material surface coatings, and in particular to a flower-shaped micro-nano double-layer structure super-hydrophobic coating and a preparation method thereof. Background Art
[0002] Many materials will corrode in harsh working environments, which will deteriorate the performance of the materials. Metal materials such as iron, copper, aluminum and stainless steel are prone to chemical or electrochemical corrosion in harsh working environments such as water, acid, alkali and salt, which will deteriorate the performance of metal materials. Since corrosion is initiated at the interface between the water medium and the material, it is possible to change the interface effect of the material and give the material surface super-hydrophobicity, which can prevent the material from corrosion, thereby extending the service life of the material and expanding the application range of engineering metals.
[0003] Superhydrophobic surface originally originated from the surface of lotus leaf. Related studies have shown that there are micron-scale and nano-scale structures on the surface of lotus leaf. The synergistic effect of surface micro-nanostructure is the key factor for the material surface to have superhydrophobic properties. Therefore, the preparation of surface coating with micro-nano rough structure is conducive to achieving surface superhydrophobicity. However, superhydrophobic surface coatings often have poor mechanical stability problems such as poor wear resistance and poor bonding with the substrate, which brings great challenges to the practical application of superhydrophobic materials. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to propose a method for preparing a flower-shaped micro-nano double-layer structured super-hydrophobic coating, which can prepare a super-hydrophobic coating with excellent wear resistance and strong bonding with the substrate, thereby solving the problem of poor mechanical stability of the existing super-hydrophobic surface.
[0005] Another object of the present invention is to provide a flower-shaped micro-nano double-layer structure super-hydrophobic coating, which is prepared by the above-mentioned preparation method. The super-hydrophobic coating of the present invention has excellent mechanical stability and super-hydrophobic properties.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] A method for preparing a flower-shaped micro-nano double-layer structure super-hydrophobic coating comprises the following steps:
[0008] (1) adding a bonding powder to a solvent and mixing the mixture thoroughly, spraying the mixture onto the surface of a substrate, and drying the mixture to obtain a base layer; the bonding powder is glass powder or thermoplastic powder;
[0009] (2) adding polydimethylsiloxane and reduced iron powder to the n-heptane solution in sequence, stirring evenly, to obtain a modified mixed solution;
[0010] (3) washing and drying the modified mixed solution in sequence to obtain a modified reduced iron powder;
[0011] (4) coating the modified reduced iron powder on the surface of the base layer and performing heat treatment to form a super hydrophobic surface layer on the surface of the base layer, thereby obtaining a flower-like micro-nano double-layer structure super hydrophobic coating.
[0012] Preferably, in step (2), the usage ratio of the polydimethylsiloxane, the reduced iron powder and the n-heptane solution is 1 g: (5-10 g): (10-30 ml).
[0013] Preferably, the operation method of step (2) is as follows: add polydimethylsiloxane to the n-heptane solution, stir magnetically for 5 to 10 minutes at a stirring speed of 300 to 600 rpm, then add reduced iron powder, stir magnetically for 30 to 60 minutes at a stirring speed of 300 to 600 rpm to obtain a modified mixed solution.
[0014] Preferably, step (3) comprises the following steps:
[0015] Add n-heptane to the modified mixed solution for stirring and cleaning, the cleaning time is 5 to 10 minutes, and the stirring speed is 300 to 600 rpm;
[0016] The cleaned modified mixed solution is dried at a temperature of 70 to 150° C. for 2 to 4 hours.
[0017] Preferably, in step (1), the thermoplastic powder is any one or more of polyethylene terephthalate powder, polyphenylene sulfide powder, and polyetheretherketone powder (PEEK powder).
[0018] Preferably, in step (1), the mass ratio of the bonding powder to the volume of the solvent is 1 g:(5-15 ml).
[0019] Preferably, in step (1), the method of mixing the bonding powder and the solvent is as follows:
[0020] The mixture was stirred by magnetic force for 5 to 15 minutes at a stirring speed of 300 to 600 rpm, and then subjected to ultrasonic treatment for 5 to 10 minutes.
[0021] Preferably, in step (1), the drying temperature is 100 to 150° C., and the drying time is 10 to 30 min;
[0022] In step (1), the solvent is ethanol.
[0023] Preferably, in step (4), the heat treatment temperature is 300-540° C., the holding time is 200-2000 min, and the heating rate is 5-15° C. / min.
[0024] Preferably, the thickness of the base layer is 10-50 μm.
[0025] A flower-shaped micro-nano double-layer structure super-hydrophobic coating is prepared by the above-mentioned preparation method of the flower-shaped micro-nano double-layer structure super-hydrophobic coating. The flower-shaped micro-nano double-layer structure super-hydrophobic coating comprises a base layer and a super-hydrophobic surface layer which are arranged in sequence from bottom to top.
[0026] The technical solution provided by the embodiments of the present application may have the following beneficial effects:
[0027] 1. The flower-shaped micro-nano double-layer structure super-hydrophobic coating prepared by the technical scheme is a modified super-hydrophobic material based on reduced iron powder. The air layer existing in the super-hydrophobic surface micro-nano structure can block the direct contact between water and the substrate. When the coating is placed underwater, a layer of silver air layer appears on the surface. This air layer can effectively hinder the migration of ions to the coating surface, so that the super-hydrophobic coating has excellent corrosion resistance, and the application of iron-based materials is further expanded.
[0028] 2. The super-hydrophobic coating of the technical solution has excellent mechanical stability. The technical solution can not only solve the problem of weak bonding between the super-hydrophobic surface layer and the substrate by using glass powder or thermoplastic powder as the intermediate layer between the adhesion substrate and the super-hydrophobic surface layer, but also its adhesion can make the coating applied to a variety of substrate surfaces. In addition, the super-hydrophobic coating prepared by the technical solution also has excellent wear resistance, corrosion resistance and antifouling properties.
[0029] 3. The solvent used in the preparation process of the super-hydrophobic coating provided by this technology is non-toxic, green and environmentally friendly, with a simple preparation process, low cost, high economic benefits, and conducive to industrial large-scale production. In terms of application, it can be applied to the surfaces of medical equipment, automobile engines, car bodies and other mechanical parts, ships and other materials, especially in the anti-corrosion and anti-pollution of iron-based materials, which can extend the service life of the material, reduce material consumption, save maintenance costs, and has important application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of the contact angle of the super-hydrophobic coating prepared in Example 1 of the present invention;
[0031] Figure 2 This is a SEM top view of the super-hydrophobic coating prepared in Example 1 of the present invention;
[0032] Figure 3 This is a SEM cross-sectional view of the super-hydrophobic coating prepared in Example 1 of the present invention;
[0033] Figure 4 This is a cross-sectional local component test diagram of the super-hydrophobic coating prepared in Example 1 of the present invention;
[0034] Figure 5 This is a test result diagram of a salt spray test of the super-hydrophobic coating prepared in Example 1 of the present invention;
[0035] Figure 6 This is a graph showing the mechanical stability test results of the super-hydrophobic coating prepared in Example 1 of the present invention;
[0036] Figure 7 Schematic diagram of the antifouling performance testing process of the super-hydrophobic coating prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0037] In order to facilitate the understanding of the present invention, the present invention is described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0038] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. Raw materials used without specifying the manufacturer are all conventional products that can be obtained through commercial purchase.
[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0040] The technical solution of the present invention is further explained below in conjunction with specific implementation methods.
[0041] A method for preparing a flower-shaped micro-nano double-layer structure super-hydrophobic coating comprises the following steps:
[0042] (1) adding a bonding powder to a solvent and mixing the mixture thoroughly, spraying the mixture onto the surface of a substrate, and drying the mixture to obtain a base layer; the bonding powder is glass powder or thermoplastic powder;
[0043] (2) adding polydimethylsiloxane (PDMS) and reduced iron powder to the n-heptane solution in sequence, stirring evenly, to obtain a modified mixed solution;
[0044] (3) washing and drying the modified mixed solution in sequence to obtain a modified reduced iron powder;
[0045] (4) coating the modified reduced iron powder on the surface of the base layer and performing heat treatment to form a super hydrophobic surface layer on the surface of the base layer, thereby obtaining a flower-like micro-nano double-layer structure super hydrophobic coating.
[0046] It is worth noting that the super-hydrophobic coating prepared by the present technical solution is a modified super-hydrophobic material based on iron. The air layer existing in the super-hydrophobic surface micro-nano structure can block the direct contact between water and metallic iron. When the coating is placed underwater, a layer of silver air layer appears on the surface. This air layer can effectively hinder the migration of ions to the coating surface, making the super-hydrophobic iron-based material have excellent corrosion resistance, and the application of iron-based materials is further expanded.
[0047] The preparation method of the technical scheme first builds a layer of base on the substrate surface, then the reduced iron powder (i.e., modified substance) modified by PDMS is coated on the base surface, and finally the coating is heat-treated to obtain a flower-like micro-nano double-layer structure super-hydrophobic coating. The principle of realizing super-hydrophobicity and corrosion resistance of coating in the technical scheme is mainly to build a micro-nano structure on the surface, and the reduced iron powder is under the high-temperature heating effect, and the reduced iron powders contacting each other diffuse and bond agglomerate to form a dense and irregularly shaped micron agglomerate, with obvious micron-level rough structure, these micron agglomerates are further observed, and there is a dense nano-flaky and needle-shaped oxide on its surface, and the mutual coordination of micron structure and nanostructure provides many air bags to the coating surface, and these air bags hinder water from contacting with the coating solid surface, and when water drops fall on the coating surface, water drops are almost suspended in the coating surface, and the corrosion ions are effectively reduced while realizing the super-hydrophobicity of coating, and migrate to the coating surface by the aqueous medium, so that the coating surface has the performance of corrosion resistance.
[0048] The flower-like micro-nano double-layer structure super-hydrophobic coating prepared by the technical solution also has excellent mechanical stability, not only has a strong bonding force with substrate, but also has good wear resistance on the coating surface. The super-hydrophobic coating of the technical solution heats and melts glass powder or thermoplastic powder during preparation, using material to bond substrate and modifier in a molten state. At this time, glass powder or thermoplastic powder as the intermediate layer of substrate and modifier, on the one hand, can make coating and substrate firmly bonded, on the other hand, can also make glass powder or thermoplastic powder and modifier between wrapping or half-wrapped physical bonding, strengthen the close combination between modified particles.
[0049] It should be pointed out that reduced iron powder is a gray or black powder mainly containing elemental iron, also known as "double absorbent", which is generally produced by reducing ferroferric oxide in a hydrogen or carbon monoxide flow under high heat conditions. Reduced iron powder is in powder form, with a very loose microstructure and a large surface area.
[0050] Preferably, the particle size of the reduced iron powder selected in the present technical solution is 80 to 200 meshes.
[0051] Specifically, before spraying the base layer in step (1), impurities on the surface of the substrate are first removed to enhance the bonding force between the bonding powder and the substrate, thereby increasing the adhesion of the entire super-hydrophobic coating to the substrate.
[0052] Specifically, the material of the substrate is a metal material or an inorganic non-metal material.
[0053] Preferably, in step (4), the method of coating the modified substance on the surface of the base layer includes any one of sieving, spraying and sprinkling. Among them, the sieving method is to place the base layer on a horizontal plane, and use a screen to cover a layer of the modified substance on the surface of the base layer, and the screen used can be a 200-800 mesh particle size; the spraying or sprinkling method is to add the modified substance to the ethanol solution, use a stirrer to fully mix, and then spray or sprinkling. Preferably, the ratio of the modified substance to the ethanol solution is 3g: (5-10ml), which can coat the modified substance on the surface of the base layer and facilitate subsequent heat treatment.
[0054] Further explanation, in step (2), the usage ratio of the polydimethylsiloxane, the reduced iron powder and the n-heptane solution is 1g:(5-10g):(10-30ml). Within this ratio range, the PDMS-wrapped modified reduced iron powder can be obtained.
[0055] Further explanation, the operation method of step (2) is as follows: add polydimethylsiloxane (PDMS) to the n-heptane solution, stir magnetically for 5 to 10 minutes at a stirring speed of 300 to 600 rpm, then add reduced iron powder, stir magnetically for 30 to 60 minutes at a stirring speed of 300 to 600 rpm to obtain a modified mixed solution.
[0056] The technical solution adds polydimethylsiloxane (PDMS) to an n-heptane solution, and stirs it magnetically for 5 to 10 minutes at a stirring speed of 300 to 600 rmp / min to fully dissolve it in the n-heptane solution; then adds reduced iron powder, and stirs it magnetically for 30 to 60 minutes at a stirring speed of 400 to 600 rmp / min to obtain a modified mixed solution, and the reduced iron powder is modified by using the PDMS in the solution, thereby reducing the solid surface energy of the reduced iron powder.
[0057] To further illustrate, step (3) includes the following steps:
[0058] To wash away excess PDMS, n-heptane (10-20 ml) was added to the modified mixed solution for stirring and washing. The washing time was 5-10 min and the stirring speed was 300-600 rpm / min.
[0059] The cleaned modified mixed solution is dried at a temperature of 70 to 150° C. for 2 to 4 hours.
[0060] Further explanation, in step (1), the thermoplastic powder is any one or more combinations of polyethylene terephthalate powder (PET powder), polyphenylene sulfide powder (PPS powder), and polyetheretherketone powder (PEEK powder).
[0061] Further explanation, in step (1), the mass ratio of the bonding powder to the volume ratio of the solvent is 1g:(5-15ml). Within this ratio, a better spraying effect can be obtained, and it is beneficial to dry and remove the solvent later; exemplary mass ratios of the bonding powder to the volume ratio of the solvent are 1g:5ml, 1g:6ml, 1g:7ml, 1g:8ml, 1g:9ml, 1g:10ml, 1g:11ml, 1g:12ml, 1g:13ml, 1g:14ml, 1g:15ml, but not limited thereto.
[0062] Further explanation, in step (1), the method of mixing the bonding powder and the solvent is as follows:
[0063] The bonding powder is fully mixed in the solvent by magnetic stirring for 5 to 15 minutes at a stirring speed of 300 to 600 rpm and then ultrasonic treatment for 5 to 10 minutes.
[0064] Further explanation, in step (1), the drying temperature is 100-150°C, and the drying time is 10-30 minutes;
[0065] In step (1), the solvent is ethanol.
[0066] It is worth noting that the drying method of step (1) is as follows: the sample is placed in an oven for drying at a temperature of 100-150°C for 10-30 minutes. After drying, a base layer is obtained on the surface of the substrate, which is used as an adhesive.
[0067] Further explanation, in step (4), the temperature of heat treatment is 300-540°C, the holding time is 200-2000 min, and the heating rate is 5-15°C / min.
[0068] It is worth noting that the heat treatment method of this technical solution is as follows: the substrate coated with the modifier is placed in a heat treatment furnace, and the heat treatment is carried out at a temperature of 300-540°C for 200-2000min, and the heating rate is 5-15°C / min, and the temperature is taken out when it drops to room temperature. The heat treatment temperature of this technical solution should be higher than the melting point temperature of the base layer, so that the base layer can be melted during the heat treatment process, so that the base layer can give full play to the role of bonding, and then improve the mechanical stability of the super-hydrophobic coating. Therefore, in order to ensure that the base layer can be completely melted, the heat treatment temperature should be higher than the melting point temperature of the base layer by more than 20°C.
[0069] In further explanation, the thickness of the base layer is 10 to 50 μm.
[0070] It is worth noting that the thickness of the base layer of the technical solution is controlled between 10~50 μm, not only can the bonding force between super-hydrophobic surface layer and substrate be improved, and the super-hydrophobic performance of flower-shaped micro-nano double-layer structure super-hydrophobic coating can be improved, if coating thickness is too thin (<10 μm), it can cause base adhesion to decline, and the bonding powder of base layer is difficult to wrap up modifier, when coating is too thick (>50 μm), the bonding powder of base layer is too much, resulting in the transition wrapping of modifier, the modifier of heating and melting rear surface is covered by base layer, which is unfavorable for forming super-hydrophobic surface structure. The technical solution can specifically control the base thickness by controlling the consumption of spraying solution.
[0071] A flower-shaped micro-nano double-layer structure super-hydrophobic coating is prepared by the above-mentioned preparation method of the flower-shaped micro-nano double-layer structure super-hydrophobic coating. The flower-shaped micro-nano double-layer structure super-hydrophobic coating comprises a base layer and a super-hydrophobic surface layer which are arranged in sequence from bottom to top.
[0072] It is worth noting that the flower-shaped micro-nano double-layer structure super-hydrophobic coating of the present technical solution is an iron-based super-hydrophobic coating with a micro-nano structure, which has excellent corrosion resistance, mechanical stability and anti-fouling properties. It can be used in offshore platforms, underwater detectors, medical equipment and ships, etc., and further expands the application of iron-based materials, especially in the corrosion and pollution prevention of iron-based materials, prolongs the service life of the material, reduces loss, reduces maintenance costs, and has good economic benefits.
[0073] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0074] Example 1
[0075] The preparation method of the flower-shaped micro-nano double-layer structure super-hydrophobic coating of this embodiment comprises the following steps:
[0076] (1) Preparing a base layer: Before preparation, the glass substrate is placed in ethanol, acetone, and deionized water solutions in sequence for ultrasonic cleaning and drying for later use; 2 g of glass powder is added to 10 ml of ethanol solution, stirred for 10 min using a magnetic stirrer, and then ultrasonically treated in an ultrasonic cleaner for 10 min to fully mix, wherein the stirring speed is 600 rpm / min, and after fully mixing, the solution is sprayed onto the surface of the glass substrate using a spray gun for drying, the drying temperature is 120° C., and the drying time is 10 min. After drying, a uniform glass powder base layer is obtained on the surface of the glass substrate;
[0077] (2) Add 1 g of PDMS to 10 ml of n-heptane solution, stir with a stirrer for 10 min at a stirring speed of 400 rpm. After PDMS is fully dissolved in n-heptane, add 5 g of reduced iron powder, and continue stirring at a stirring speed of 400 rpm for 30 min to obtain a modified mixed solution;
[0078] (3) adding 20 ml of n-heptane solution to the modified mixed solution of step (2) for stirring and washing at a stirring speed of 600 rpm for 10 min. To remove the solvent, the washed solution was placed in an oven and dried at 70° C. for 4 h to obtain a PDMS-modified reduced iron powder;
[0079] (4) 6 g of the modified reduced iron powder of step (3) is uniformly mixed in 10 ml of ethanol solution, and sprayed on the surface of the base layer in step (1). The coating is placed in a 540°C heat treatment furnace for 200 min at a heating rate of 10°C / min. After the insulation time is over, it is taken out after cooling to room temperature to form a super-hydrophobic surface layer on the surface of the base layer, thereby obtaining a flower-shaped micro-nano double-layer structure super-hydrophobic coating.
[0080] Example 2
[0081] The preparation method of the flower-shaped micro-nano double-layer structure super-hydrophobic coating of this embodiment comprises the following steps:
[0082] (1) Preparing a base layer: Before preparation, the copper sheet (i.e., the polar region) is placed in ethanol, acetone, and deionized water solutions for ultrasonic cleaning and drying for later use; 1 g of polyethylene terephthalate powder (PET powder) is added to 10 ml of ethanol solution, stirred for 10 min using a magnetic stirrer, and then ultrasonically treated for 5 min in an ultrasonic cleaner to fully mix, wherein the stirring speed is 500 rpm. After fully mixing, the solution is sprayed onto the surface of the copper sheet substrate using a spray gun for drying, the drying temperature is 100° C., and the drying time is 30 min. After drying, a uniform PET powder base layer is obtained on the surface of the copper sheet;
[0083] (2) Add 1 g of PDMS to 19 ml of n-heptane solution and stir for 10 min using a stirrer at a stirring speed of 400 rpm. After the PDMS is fully dissolved in n-heptane, add 7.5 g of reduced iron powder and continue stirring at a stirring speed of 400 rpm for 50 min to obtain a modified mixed solution.
[0084] (3) adding 15 ml of n-heptane solution to the modified mixed solution of step (2) for stirring and washing, the stirring speed is 600 rpm, and the stirring and washing time is 10 min. To remove the solvent, the washed solution is placed in an oven and dried at a temperature of 80° C. for 2 h to obtain a PDMS-modified reduced iron powder;
[0085] (4) 6 g of the reduced iron modification of step (3) was uniformly mixed in 16 ml of ethanol solution, and the mixture was drop-coated on the surface of the base layer in step (1). The coating was placed in a 300°C heat treatment furnace and kept warm for 1440 min at a heating rate of 10°C / min. After the heat preservation time was over, the coating was taken out after cooling to room temperature to obtain a flower-shaped micro-nano double-layer structure super-hydrophobic coating.
[0086] Example 3
[0087] The preparation method of the flower-shaped micro-nano double-layer structure super-hydrophobic coating of this embodiment comprises the following steps:
[0088] (1) Preparing a base layer: Before preparation, the aluminum sheet substrate is placed in ethanol, acetone, and deionized water solution in sequence for ultrasonic cleaning and drying for later use; 1 g of polyphenylene sulfide powder (PPS powder) is added to 15 ml of ethanol solution, stirred for 10 min using a magnetic stirrer, and then ultrasonically treated in an ultrasonic cleaner for 5 min to fully mix, wherein the stirring speed is 400 rpm. After fully mixing, the solution is sprayed onto the surface of the aluminum sheet substrate using a spray gun for drying, the drying temperature is 140° C., and the drying time is 10 min. After drying, a uniform PPS powder base layer is obtained on the surface of the aluminum sheet;
[0089] (2) Add 1 g of PDMS to 29 ml of n-heptane solution, stir with a stirrer for 10 min at a stirring speed of 600 rpm. After PDMS is fully dissolved in n-heptane, add 10 g of reduced iron powder, and continue stirring at a stirring speed of 600 rpm for 60 min to obtain a modified mixed solution;
[0090] (3) adding 10 ml of n-heptane solution to the modified mixed solution of step (2) for stirring and washing, the stirring speed is 600 rpm, and the stirring and washing time is 10 min. To remove the solvent, the washed solution is placed in an oven and dried at a temperature of 100° C. for 3 h to obtain a PDMS-modified reduced iron powder;
[0091] (4) 3 g of the modified reduced iron powder in step (3) was uniformly mixed in 10 ml of ethanol solution and sprayed on the surface of the base layer in step (1). The coating was placed in a 320°C heat treatment furnace and kept warm for 1440 min at a heating rate of 10°C / min. After the insulation time was over, it was cooled to room temperature and then taken out to obtain a flower-shaped micro-nano double-layer structure super-hydrophobic coating.
[0092] Example 4
[0093] The preparation method of the flower-shaped micro-nano double-layer structure super-hydrophobic coating of this embodiment comprises the following steps:
[0094] (1) Preparing a base layer: Before preparation, a stainless steel sheet substrate is placed in ethanol, acetone, and deionized water solution in sequence for ultrasonic cleaning and drying for later use; 2 g of polyetheretherketone powder (PEEK powder) is added to 15 ml of ethanol solution, stirred with a magnetic stirrer for 10 min, and then ultrasonically treated in an ultrasonic cleaner for 10 min to fully mix, wherein the stirring speed is 500 rpm / min, and after fully mixing, the solution is sprayed onto the surface of the stainless steel substrate using a spray gun for drying, the drying temperature is 120° C., and the drying time is 10 min. After drying, a uniform PEEK powder base layer is obtained;
[0095] (2) Add 2 g of PDMS to 25 ml of n-heptane solution, stir with a stirrer for 10 min at a stirring speed of 600 rpm. After PDMS is fully dissolved in n-heptane, add 7 g of reduced iron powder, and continue stirring at a stirring speed of 600 rpm for 60 min to obtain a modified mixed solution;
[0096] (3) adding 20 ml of n-heptane solution to the modified mixed solution of step (2) for stirring and washing, the stirring speed is 600 rpm, and the stirring and washing time is 10 min. To remove the solvent, the washed solution is placed in an oven and dried at a temperature of 100° C. for 4 h to obtain a PDMS-modified reduced iron powder;
[0097] (4) The reduced iron powder modified product of step (3) is evenly covered on the surface of the base layer in step (1) using a 200-mesh screen, and the coating is then placed in a 360° C. heat treatment furnace for 2000 min at a heating rate of 10° C. / min. After the insulation time is over, it is cooled to room temperature and then taken out to obtain a flower-shaped micro-nano double-layer structure super-hydrophobic coating.
[0098] Specifically, the water contact angle, SEM top view, SEM cross-sectional view and component test of the surface of the flower-shaped micro-nano double-layer structure super-hydrophobic coating prepared in Example 1 were detected. The test results are as follows: Figure 1-4 The super hydrophobic coating prepared in Example 1 was subjected to corrosion resistance test, mechanical stability test and antifouling performance test. The test results are shown in Figure 5-7 shown.
[0099] Figure 1 This is a schematic diagram of the contact angle profile of the surface of the flower-shaped micro-nano double-layer structure superhydrophobic coating (hereinafter referred to as the superhydrophobic coating) prepared in Example 1. It can be seen that the water contact angle on the surface of the superhydrophobic coating can reach 158°, the coating surface has a higher contact angle, and the coating surface has superhydrophobic properties.
[0100] Figure 2 and Figure 3 The SEM top view and SEM cross-sectional view of the surface of the super hydrophobic coating prepared in Example 1 are respectively. Figure 2 It can be seen from a that the surface of the super-hydrophobic coating is composed of irregularly shaped micron clusters and has obvious micron-level rough structures. These rough structures are reduced iron powder (particle size 200 mesh) after heat treatment. Under the effect of high temperature heating, the reduced iron powders in contact with each other diffuse and bond together. The micron clusters on its surface are magnified and analyzed. Figure 2 In b, it can be clearly seen that there are a large number of nano-sheet and filamentous oxides on the surface of the micron cluster. These nano-scale oxides are densely distributed on the surface of the micron-sized reduced iron powder particles and construct a micro-nano-scale hierarchical structure on the surface of the super-hydrophobic coating. Figure 3 The cross-sectional structure of the super-hydrophobic coating can be seen. The middle bonding layer (dashed line area) constructed by glass powder can be clearly seen in the figure. The glass powder after high-temperature heat treatment is mixed with the substrate and the micron-sized reduced iron powder without obvious boundary layer. Figure 3 The white box area) is scanned for elements, and the results are as follows Figure 4 As shown: the main elements on the glass powder intermediate layer are O, Na, Si, K, Ca (from glass powder) and a small amount of Fe (6.49%, from reduced iron powder). Element analysis shows that the glass powder intermediate layer (i.e., the base layer) and the reduced iron powder on the coating surface are effectively diffused and bonded under high-temperature heat treatment. The existence of the glass powder intermediate layer effectively improves the problem of poor compatibility between the reduced iron powder and the substrate surface, and improves the mechanical stability of the coating surface.
[0101] Figure 5 The test results of the salt spray test of the super hydrophobic coating prepared in Example 1 of the present invention are shown in Figure 1. The neutral salt spray test is used to simulate the corrosive environment of marine applications. The salt spray test is carried out for 3 days at a temperature of 35°C and a concentration of 5wt% NaCl, and the contact angle of the coating surface is measured every other day. Figure 5 It can be seen that the contact angle of the coating is still greater than 150° after 24 hours of salt spray test, and the contact angle is lower than 150° after 48 hours, and the contact angle is lower than about 90° until 72 hours, indicating that the superhydrophobic coating has excellent corrosion resistance.
[0102] Figure 6 The mechanical stability test results of the super-hydrophobic coating obtained in Example 1. A wear test was performed using a sample with a size of 2.5 cm × 4.0 cm. During the test, the sample was inverted on the surface of silicon carbide sandpaper (400#), and the coating surface was scratched with sandpaper in a fixed direction at a speed of 1 cm / s under a load of 100 g, with a movement of 20 cm as a cycle, and the change of the surface WCA value was recorded once after each cycle. As can be seen from the figure, the coating has a contact angle of less than 150 ° after 8 cycles, and the angle is greater than 140 °, and there is still a high contact angle, which reflects the excellent mechanical stability of the coating.
[0103] Figure 7 The figure is a test diagram of the antifouling performance of the super hydrophobic coating surface prepared in Example 1. The super hydrophobic coating surface is tilted at a certain angle, a certain amount of sand is evenly sprinkled on the end of the sample, and droplets are sucked with a needle to perform the antifouling performance test. Figure 7 It can be seen from ad that after the droplet falls freely, it rolls down quickly on the surface and finally rolls out of the super-hydrophobic sample surface completely, taking away the sand along the way, and the surface sand is completely cleaned. It takes less than 1ml of water to clean all the sand on the surface of the super-hydrophobic sample, which shows that the adhesion between the sand and the surface of the super-hydrophobic coating is very low, and the rolling water droplets can easily take away the pollutants. The coating shows excellent anti-fouling performance and has potential application value in the field of anti-fouling.
[0104] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific implementations of the present invention without paying creative labor, and these methods will fall within the scope of protection of the present invention.
Claims
1. A method for preparing a flower-shaped micro-nano double-layer structure super-hydrophobic coating, characterized in that: The following steps are involved: (1) adding a bonding powder to a solvent and mixing them thoroughly, spraying the mixed powder onto the surface of the substrate, and drying the mixed powder to obtain a base layer; the bonding powder is glass powder or thermoplastic powder; (2) adding polydimethylsiloxane and reduced iron powder to the n-heptane solution in sequence, stirring evenly, to obtain a modified mixed solution; (3) washing and drying the modified mixed solution in sequence to obtain a modified reduced iron powder; (4) coating the modified reduced iron powder on the surface of the base layer and performing heat treatment to form a super hydrophobic surface layer on the surface of the base layer, thereby obtaining a flower-like micro-nano double-layer structure super hydrophobic coating.
2. The method for preparing the flower-shaped micro-nano double-layer structure super-hydrophobic coating according to claim 1, characterized in that: In step (2), the usage ratio of the polydimethylsiloxane, the reduced iron powder and the n-heptane solution is 1g:(5-10g):(10-30ml).
3. The method for preparing the flower-shaped micro-nano double-layer structure super-hydrophobic coating according to claim 1, characterized in that: The operation method of step (2) is as follows: add polydimethylsiloxane to the n-heptane solution, stir magnetically for 5 to 10 minutes at a stirring speed of 300 to 600 rpm, then add reduced iron powder, stir magnetically for 30 to 60 minutes at a stirring speed of 300 to 600 rpm to obtain a modified mixed solution.
4. The method for preparing the flower-shaped micro-nano double-layer structure super-hydrophobic coating according to claim 1, characterized in that: Step (3) comprises the following steps: Add n-heptane to the modified mixed solution for stirring and cleaning, the cleaning time is 5 to 10 minutes, and the stirring speed is 300 to 600 rpm; The cleaned modified mixed solution is dried at a temperature of 70 to 150° C. for 2 to 4 hours.
5. The method for preparing the flower-shaped micro-nano double-layer structure super-hydrophobic coating according to claim 1, characterized in that: In step (1), the thermoplastic powder is any one or more of polyethylene terephthalate powder, polyphenylene sulfide powder, and polyetheretherketone powder (PEEK powder).
6. The method for preparing the flower-shaped micro-nano double-layer structure super-hydrophobic coating according to claim 1, characterized in that: In step (1), the mass ratio of the bonding powder to the volume ratio of the solvent is 1 g:(5-15 ml).
7. The method for preparing the flower-shaped micro-nano double-layer structure super-hydrophobic coating according to claim 1, characterized in that: In step (1), the drying temperature is 100 to 150° C. and the drying time is 10 to 30 minutes; In step (1), the solvent is ethanol.
8. The method for preparing the flower-shaped micro-nano double-layer structure super-hydrophobic coating according to claim 1, characterized in that: In step (4), the heat treatment temperature is 300-540°C, the heat preservation time is 200-2000 min, and the heating rate is 5-15°C / min.
9. The method for preparing the flower-shaped micro-nano double-layer structure super-hydrophobic coating according to claim 1, characterized in that: The thickness of the base layer is 10-50 μm.
10. A flower-shaped micro-nano double-layer structure super-hydrophobic coating, characterized in that: The super-hydrophobic coating with a flower-shaped micro-nano double-layer structure is prepared by the preparation method of any one of claims 1 to 9, wherein the super-hydrophobic coating with a flower-shaped micro-nano double-layer structure comprises a base layer and a super-hydrophobic surface layer arranged in sequence from bottom to top.
Citation Information
Patent Citations
Polymer-matrix composite material with super-hydrophobic surface and preparation method thereof
CN101830098A
Flower-shaped wave-absorbing particle, wave-absorbing film, preparation method and application
CN115924983A
Super-hydrophobic anti-icing coating and preparation method thereof
CN117659749A
Powder Coating Composition For Thermoplastic Composites
US20110028638A1